2018
DOI: 10.12911/22998993/89825
|View full text |Cite
|
Sign up to set email alerts
|

Biological Stability of Water after the Biofiltration Process

Abstract: One of the most frequently implemented processes in the water treatment technology is filtration through a biosorption bed. The techniques based on biochemical processes involving bacteria result in obtaining high quality of water. There are a number of different materials used as the filler material for biological filters. Carbon deposits are the most popular, due to their high effectiveness. The problem with the use of this process is the leaching of microorganisms from the biofilm and the biological stabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 4 publications
3
3
0
Order By: Relevance
“…A similar dependency was noted in the case of total organic carbon (TOC), the content of which, after passing through the system, increased from 2.03 mg C/L to 2.93 mg C/L. Decrease of biofilm growth depends on water temperature, time duration of presence in the system, as well as type and concentration of disinfectant [32,35,36].…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…A similar dependency was noted in the case of total organic carbon (TOC), the content of which, after passing through the system, increased from 2.03 mg C/L to 2.93 mg C/L. Decrease of biofilm growth depends on water temperature, time duration of presence in the system, as well as type and concentration of disinfectant [32,35,36].…”
Section: Discussionsupporting
confidence: 61%
“…In order to maintain stability and maximally limit the risk of secondary biological water pollution, two out of three biogenes determining microorganism growth should be removed [10]. Zamorska in her research, confirmed the lack of biological stability of water injected into the water-pipe network [32].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This study showed that R2A agar stimulated the growth of a higher number of microorganisms compared to A agar. Similar results were obtained in the studies [47,48]. The composition of Agar R (with reduced peptone, yeast extract and dextrose level) combined with an extended incubation time stimulates the growth of a higher number of heterotrophic bacteria [47].…”
Section: Discussionsupporting
confidence: 79%
“…Less attention has been paid to the microbiological quality of the filtrate. In the works [55,56], small changes were shown between the quality of water directed to biofilters and flowing from the biofilter (the study was conducted for surface water treated with ozonation before biofiltration).…”
Section: Discussionmentioning
confidence: 99%